Clinical Classification of Diseases and Conditions of Mammary Glands in Children and Adolescents - Marina L. Travina; Alexander G. Popov; Sergei A. Popov; Elena V. Kulikova (Вопросы современной педиатрии)
The article describes the proposed current clinical classification of breast diseases and pathology in childhood and adolescence. The classification is based on the analysis of data obtained from the examination and follow-up monitoring of 6,126 children for up to 8 years. The clinical classification is recommended for widespread use in the work of primary care physicians who conduct follow-up monitoring. The use of this classification creates groups for referral to specialists for further examination and further treatment and follow-up monitoring. The classification is based on the separation of physiological (normal conditions) and pathological processes, as well as on temporary deviations from normal development (temporary conditions not leading to pathological processes) and anomalies in development of mammary glands and nipple-areolar complex. If any abnormalities are suspected, a patient shall be sent to a mammologist for further examination and US scanning. Control of growth and development of mammary glands in childhood and adolescence ensures early detection of abnormalities and allows necessary remedial measures to protect reproductive health.